Electronics : a survey of electrical engineering principles - Boylestad, Robert; Nashelsky, Louis (Englewood Cliff Prentice Hall, 1996)
To help readers better understand current technology and develop a framework for understanding future growth in the electronics area, this book covers a broad spectrum of subject matter beginning with background chapters, moving to material on basic electronics areas, and concluding with a variety of applications. The book updates coverage to reflect the most recent, relevant developments in the field, including PSpice technology, and expands coverage of many areas, including electronic devices, op-amps and digital systems.